IMPROVING INFORMED MODEL PRESENTATION AND MODELING SEQUENCE - Sadullayeva, Sabina (Журнал иностранных языков и лингвистики, 2024)
This article describes the parameters and variables important to the object, the relationships between them, the information that describes the input and output of the object, and the variable model that provides complete information about the object’s possible It is about an informative model that fully classifies the process of modeling the states of.